2019
DOI: 10.1159/000496033
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Human Thrombospondin-1 to the Pathogenesis of Gram-Positive Bacteria

Abstract: A successful colonization of different compartments of the human host requires multifactorial contacts between bacterial surface proteins and host factors. Extracellular matrix proteins and matricellular proteins such as thrombospondin-1 play a pivotal role as adhesive substrates to ensure a strong interaction with pathobionts like the Gram-positive Streptococcus pneumoniae and Staphylococcus aureus. The human glycoprotein thrombospondin-1 is a component of the extracellular matrix and is highly abundant in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 132 publications
1
6
0
Order By: Relevance
“…The functions of thrombospondin-1 in immune regulation are complex and are mediated by several thrombospondin-1 receptors (Forslow et al 2007 ; Martin-Manso et al 2008 ; Sarfati et al 2008 ; Stein et al 2016 ; Kaur et al 2021 ). Correspondingly, loss of Thbs1 in mice has been demonstrated to either increase or decrease their survival following exposure to different bacterial, viral, or fungal pathogens (Lawler et al 1998 ; Martin-Manso et al 2012a ; Qu et al 2018 ; Binsker et al 2019 ; Arun et al 2020 ).…”
Section: Insights Into Protective Functions Of Thbs1 In Micementioning
confidence: 99%
“…The functions of thrombospondin-1 in immune regulation are complex and are mediated by several thrombospondin-1 receptors (Forslow et al 2007 ; Martin-Manso et al 2008 ; Sarfati et al 2008 ; Stein et al 2016 ; Kaur et al 2021 ). Correspondingly, loss of Thbs1 in mice has been demonstrated to either increase or decrease their survival following exposure to different bacterial, viral, or fungal pathogens (Lawler et al 1998 ; Martin-Manso et al 2012a ; Qu et al 2018 ; Binsker et al 2019 ; Arun et al 2020 ).…”
Section: Insights Into Protective Functions Of Thbs1 In Micementioning
confidence: 99%
“…PECAM1, an endothelial cell adhesion molecule, played a potentially protective role in lung injury and acute respiratory distress syndrome ( 84 , 85 ). THBS1 also has been found to be implicated in the pathogenesis of gram-positive bacteria and the development of lung injury ( 86 , 87 ). For instance, THBS1 loss reduced mouse survival rate, increased lung bacterial burden and lung microvascular permeability, impaired host defense against Pseudomonas aeruginosa ( P. aeruginosa ), and potentiated inflammatory injury during P. aeruginosa acute intrapulmonary infection ( 87 ), while P. aeruginosa is a common pathogen of pneumonia in FMD ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice and primates indicated specific roles for Thbs1 in reproduction (Bender et al 2019; Greenaway et al 2007) and in the ability of adult mice, rats and pigs to repair dermal wounds and survive exposure to ischemic injuries or genotoxic stress (Isenberg et al 2007, 2008a, b; Soto‐Pantoja et al 2015). Loss of Thbs1 in mice also alters their survival following exposure to several pathogens (Arun et al 2020; Binsker et al 2019; Lawler et al 1998; Martin‐Manso et al 2012; Qu et al 2018). Loss of Thbs1 impairs survival for some of these stresses while improving survival or recovery from other stresses.…”
Section: Discussionmentioning
confidence: 99%